Empiric Versus Clarithromycin Resistance–Guided Therapy for Helicobacter pylori Based on Polymerase Chain Reaction Results in Patients With Gastric Neoplasms or Gastric Mucosa-Associated Lymphoid Tissue Lymphoma: A Randomized Controlled Trial. Issue 9 (16th September 2020) - Kim, Jue Lie; Cho, Soo-Jeong; Chung, Su Jin; Lee, Ayoung; Choi, Jinju; Chung, Hyunsoo; Kim, Sang Gyun
Abstract : INTRODUCTION: We investigated to compare the effect of empirical therapy vs clarithromycin resistance–guided tailored therapy (tailored therapy) for eradication of Helicobacter pylori . METHODS: In this prospective, single center, open-label randomized controlled trial, we enrolled 72 patients with H. pylori infection from January 2019 through June 2019 in Korea. The patients were randomly assigned to both groups received empirical (n = 36) or tailored therapy (n = 36). Empirical therapy was defined as triple therapy with esomeprazole, amoxicillin, and clarithromycin for 10 days irrespective of clarithromycin resistance. Tailored therapy was triple or quadruple therapy with esomeprazole, metronidazole, tetracycline, and bismuth for 10 days based on genotype markers of resistance determined by gastric biopsy. Resistance-associated mutations in 23S rRNA were confirmed by multiplex polymerase chain reaction. Eradication status was assessed by 13 C-urea breath test, and the primary outcome was eradication rates. RESULTS: H . pylori was eradicated in 27 patients (75.0%), given empirical therapy and 32 patients (88.9%) treated with tailored therapy ( P = 0.136) in intention-to-treat analysis. In per protocol analysis, the eradication rate was 97.0% and 81.8% in tailored vs empirical groups ( P = 0.046). Although clarithromycin-resistant H. pylori was eradicated in 3/9 (33.3%) with empirical therapy, it was treated in 11/12 (91.7%) with tailored therapy ( P = 0.009). There was no difference in compliance between 2 groups. The rate of adverse events of the tailored group was higher than that of the empirical group ( P = 0.036) because quadruple therapy had more side effects than those of triple therapy ( P = 0.001). DISCUSSION: Tailored therapy based on polymerase chain reaction is a good alternative to increase eradication rates in a region of high prevalence of clarithromycin resistance (see Visual Abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A342 ).